"Super‐Reducing" Photocatalysis: Consecutive Energy and Electron Transfers with Polycyclic Aromatic Hydrocarbons. Issue 35 (23rd June 2017) - Brasholz, Malte
Abstract : Donation welcome : Recent developments in visible‐light photocatalysis allow the utilization of increasingly negative reduction potentials. Successive energy and electron transfer with polycyclic aromatic hydrocarbons enables the catalytic formation of strongly reducing arene radical anions, classical stoichiometric reagents for one‐electron reduction in organic synthesis.